Barley diseases and their management: An Indian perspective - Gangwar, Om Prakash; Bhardwaj, Subhash Chander; Singh, Gyanendra Pratap; Prasad, Pramod; Kumar, Subodh (Journal of Cereal Research, 2018)
Barley is an important coarse cereal, cultivated in Rabi season, particularly in the states of Uttar Pradesh, Rajasthan, Madhya Pradesh, Bihar, Punjab, Haryana, Himachal Pradesh and Jammu & Kashmir.Â Currently, it covers an area of about 0.66 million hectares under rainfed and irrigated crop. Seventy percent produce is used for cattle and poultry feed, 25% in industries for manufacturing malt and malt extracts and rest 5% for human consumption. The straw is also used for animal feed, bedding and to cover roofs of houses. Barley grains demand is increasing continuously because of its various uses and high nutritive value. Therefore, a substantial yield gain will be needed over the next several decades. A number of biotic and abiotic factors pose a challenge to increase production of barley. Barley diseases prominently rusts, net blotch, spot blotch, Septoria speckled leaf blotch, stripe disease, powdery mildew, barley yellow dwarf, and molya disease are the major biotic constraints in enhancing the barley grainproduction. Other diseases like black point and smuts, are important from the industrial point of view because these deteriorate the quality of malt and beer. This review seeks to provide an overview of different barley diseases and their management.Â Doi.org/10.25174/2249-4065/2018/83844